Two-Dimensional Modelling and Validation of the Mass Flow in a Mixing Stirred Reactor - Daniela Kladeková; Renáta Oriňáková; Hans-Dieter Wiemhöfer; Annamária Krajníková; Andrej Oriňák (Nanomaterials and Nanotechnology)
The present work focuses on the computational modelling of fluid flow in a mixing stirred reactor to describe the flow pattern in two‐dimensional (2D) detail, which can be useful for optimizing the parameters of electroplating for the production of a uniform film on metallic particles in a stirred electrolytic cell. The results of modelling and simulation show that the electrolytic cell geometry and the presence of a solid electrode affect the streamline distribution. The most important parameter affecting the fluid flow is not just the position but also the size of the stirrer as well. It is concluded that the “high cell” with the “big stirrer” can be used for the electroplating of iron micro‐ and nanoparticles in the presence of the cylindrical electrode.